Job creation in Latin America and the Caribbean : recent trends and policy challenges - Pagés, Carmen (Latin American development forum., 2009)
This book analyzes recent labor market trends in Latin American countries and the factors that underlie the failure to create more--and more productive and rewarding--jobs, a failure with substantial political and social costs. The authors analyze how growth and job creation in the region's economies compare with other emerging countries, the impact of job creation and destruction on productivity growth and the creation of "good" jobs, and the relative importance and role of labor market policies in improving labor market outcomes in the region